Analisis Kasualitas Indikator Makro Kesejahteraan Masyarakat Provinsi Banten Tahun 2017-2021 - Loanna Mahintan; Sugeng Setyadi; Rizal Syaifudin (PT Wim Solusi Prima, 2023)
Community welfare is the main goal of economic development. Concrete efforts made by the Provincial Government of Banten continue to be made to improve welfare in the region. This study aims to determine the short-term relationship and long-term variables of community welfare indicators between districts/cities in Banten Province in 2017-2021. This type of research is quantitative with a descriptive approach, in which the research is systematically arranged with numbers processed from the results of secondary data sourced from the Central Bureau of Statistics, Bappeda, and Bappenas. Finally, this data measurement uses the Vector error correction model (VECM) method with test stages: (1) Stationarity Test, (2) Stability Test, (3) Optimum Lag Test, (4) Cointegration Test, (5) Granger Duration Test, and (6) VECM Estimation. The results of this study are (1) All data on the variables of this study are stationary at the 1st Difference level, (2) There is a short-term and long-term relationship between variables in this study characterized by cointegration, (3) There is a one-way causal relationship between Education and poverty, (4) There is a one-way causal relationship between Education and HDI, (5) There is a two-way causal relationship between Poverty and Unemployment, (6) There is a one-way causal relationship between Poverty and HDI, (7) There is no causal relationship between Unemployment and HDI, (8) Finally, measurement of indicators that are relevant to people's welfare.